Acting sub specie boni. (31st August 2017) - Mayr, Erasmus
Abstract : On a traditional view of human agency, intentional actions are performed sub specie boni : Agents, in acting intentionally, must see some good in what they are doing. This view has come under heavy criticism, which has partly focussed on several putative counterexamples, and partly on the view's underlying rationale. In this paper, I defend one version of the sub specie boni view and try to show that it still deserves its old standing as the "default view" about acting with an intention. For, as I argue, this view helps us to make sense of some crucial features of intentions – in particular, that we are sometimes rationally permitted to abandon intentions in the light of obstacles and costs –, for which an alternative explanation will be hard to find.